Optimisasi Rute Pengiriman Produk Komponen Otomotif (Traveling Salesman Problem) Melalui Pendekatan Heuristik - Afif, M Syahri Nur; Tsauri, M. Ibrahim Ats; Hadiwijaya, Syahrif (JURNAL TEKNIK INDUSTRI, 2022)
On -time delivery is a key KPI in the supply chain of automotive component manufacturing companies such as PT XYZ. Delays in delivery can result in large losses as customer stop line losses will be charged to the company. Delivery delays also lead to reduced customer satisfaction and increased transportation costs. Therefore, it is necessary to optimize product delivery to customers to achieve timely delivery targets, achieve customer satisfaction, and transportation cost efficiency. This study aimed to find a solution to the Traveling Salesman Problem (TSP) with the Cheapest-Insertion Heuristics (CIH) heuristic approach. Heuristic methods are methods used to solve problems by trial and error when the algorithmic approach is considered impractical and inefficient to produce a solution. The results show that the CIH method can produce an optimal route that is NIP-CHN-KID-MKI-SRI-MTAT-NIP with a minimum distance of 290 km.